Neurogenic induction of human dental pulp derived stem cells by hanging drop technique, basic fibroblast growth factor, and SHH factors - Safa Farhang; Mitra Soleimani; Maryam Ostadsharif; Nazem Ghasemi (Wolters Kluwer Medknow Publications, 2021)
Background: The progressive destruction of nerve cells in nervous system will induce neurodegenerative diseases. Recently, cell-based therapies have attracted the attention of researchers in the treatment of these abnormal conditions. Thus, the aim of this study was to provide a simple and efficient way to differentiate human dental pulp stem cells into neural cell-like to achieve a homogeneous population of these cells for transplantation in neurodegenerative diseases. Materials and Methods: In this basic research, human dental pulp stem cells were isolated and characterized by immunocytochemistry and flow cytometry techniques. In the following, the cells were cultured using hanging drop as three-dimensional (3D) and tissue culture plate as 2D techniques. Subsequently, cultured cells were differentiated into neuron cell-like in the presence of FGF and Sonic hedgehog (SHH) factors. Finally, the percentage of cells expressing Neu N and β tubulin III markers was determined using immunocytochemistry technique. Finally, all data were analyzed using the SPSS software. Results: Flow cytometry and immunocytochemistry results indicated that human dental pulp-derived stem cells were CD90, CD106-positive, but were negative for CD34, CD45 markers (P ≤ 0.001). In addition, the mean percentage of β tubulin positive cells in different groups did not differ significantly from each other (P ≥ 0.05). Nevertheless, the mean percentage of Neu N-positive cells was significantly higher in differentiated cells with embryoid bodies' source, especially in the presence of SHH than other groups (P ≤ 0.05). Conclusion: It is concluded that due to the wide range of SHH functions and the facilitation of intercellular connections in the hanging droop method, it is recommended that the use of hanging drop method and SHH factor can be effective in increasing the efficiency of cell differentiation.